Press Freedom and Corruption Perceptions: Is There a Reputational Premium? - Michael Breen; Robert Gillanders (Politics and Governance, 2020)
Many studies find a strong association between press freedom and corruption perceptions (Adsera, Boix, & Payne, 2003; Brunetti & Weder, 2003; Freille, Haque, & Kneller, 2007). However, it is possible that this relationship is driven by experts’ belief that limits on press freedom are associated with corruption. This article tests the association between press freedom and corruption perceptions using objective measures of corruption from the World Bank’s Enterprise Surveys, a series of representative surveys of the owners and top managers of private firms in the manufacturing and service sectors. Our findings suggest that there is a reputational premium associated with press freedom: Holding corruption experiences constant, corruption perceptions are improved by greater press freedom. Moreover, we find that the developed world is best placed to avail of this premium, as it is most evident in countries with low to moderate levels of corruption by global standards.